Efeito do Ca2+, Zn2+ e Mg2+ com o Ácido 1-hidroxietilideno -1,1-difosfônico como inibidor de corrosão dos aços inoxidáveis AISI 304 e AISI 430 em um meio contendo íons cloreto e sulfeto - Franco, Juliana Panceri (2020)
The performance of the commercial 1-Hydroxyethylidene-1,1-diphosphonic acid inhibitor was investigated by Potentiodynamic Polarization and Electrochemical Impedance Spectroscopy techniques in AISI 304 and AISI 430 stainless steels, immersed in a solution